Applying Authentic Learning through Cultivation of the Entrepreneurial Mindset in the Engineering Classroom - Lisa Bosman; Stephanie Fernhaber (MDPI AG, 2018)
Higher education provides plenty of opportunity for theory and in many cases, even the ability to apply theory in a laboratory setting. Yet, there remains limited opportunity for students to learn by doing through participation in authentic learning experiences. The purpose of this paper is to provide one potential solution for integrating authentic learning into the engineering classroom by cultivating the entrepreneurial mindset. As entrepreneurship serves as an integral part of the economy, developing an entrepreneurial mindset through authentic learning experiences is essential for engineers. While online discussion prompts represent a useful way for educators to facilitate student learning, less is known about how to facilitate online discussions in a way that truly cultivates an entrepreneurial mindset for engineering students. In this paper, the key intentions of entrepreneurially-minded learning are reviewed, and a guide for creating online discussions applicable to any engineering course is presented. Example online discussion prompts incorporating the entrepreneurial mindset are then shared from an Introduction to Engineering course. Results from a mixed methods survey instrument suggests positive impacts towards student perceptions of online discussions and development of the entrepreneurial mindset. Recommendations for effectively and efficiently facilitating online discussions for entrepreneurially-minded learning in the engineering classroom are offered.